EMOTIONAL ANALYSIS OF GO MOON YOUNG CHARACTERS IN THE DRAMA “IT'S OK TO NOT BE OKE” - Nur Intan Permatasari; Delfina Fatihayah; Dyah Kristyowati; Ira Resmayasari (English Education Study Program STKIP PGRI Pacitan, 2022)
This study aims to determine the emotional character of Go Moon Young, who is the main character in thedrama